Strategy of cilor agroindustry development: Case study on cilor MSMEs in South Cikarang District, Bekasi Regency - Suri, Anita; Irfan, Yusuf; Riandani, Andini Putri; Supriyanto; Melati Putri, Indah; Anandartiana Gunawan, Wawan (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Agroindustry development has an important role in increasing regional economic growth and empowering the community. This study aims to identify internal and external factors that influence Cilor agro-industry in South Cikarang District, Bekasi Regency, as well as to develop an effective development strategy. Methods: The methods used include SWOT analysis, internal-external matrix, and data collection through interviews and observation. Finding: The research results show that cilor agroindustry has great potential to be developed, but also faces several challenges. Conclusion: An appropriate development strategy is needed to maximize opportunities and overcome obstacles in the development of cilor's agro-industry Novelty/Originality of this article: The novelty in this research is the study of the Cilor agro-industry development strategy, where there is not much research that discusses similar topics which is expected to help increase the scale of the same business.